(untitled) (Research, Society and Development, 2023)
Introduction: Ventilator-associated pneumonia (VAP) arises as a complication resulting from the use of invasive mechanical ventilation (IMV) and its main cause is the aspiration of microorganisms, especially bacteria, present in the oropharynx. This condition is considered one of the most prevalent hospital infections among patients admitted to Intensive Care Units (ICUs) and is associated with a high mortality rate. Objective: The aim of the work is to analyze the importance of oral care for the prevention of VAP, identify the VAP prevention package, as well as the antiseptic recommended for oral hygiene in patients intubated in the ICU. Methodology: This is an integrative literary review, the bibliographic search was carried out using scientific articles published in national and international journals, found in the electronic databases of the Virtual Health Library (VHL) and PubMed using previously defined descriptors and registered in the Health Sciences Descriptors (DeCS), between the months of August and September 2023. Results: 624 articles were found in the databases. After analyzing the titles and abstracts, 236 articles were pre-selected and read in full. Then, 17 articles were included in the presente review. Conclusions: Following the VAP package, as well as dental care for critical patients, is essential for reducing the incidence of VAP. Most studies carried out highlight the efficiency of oral hygiene using 0.12% chlorhexidine solution.